Effects of Cobalamin (Vitamin B12) on Gentamicin Induced Nephrotoxicity in Rat - Hajihashemi, Saeed; Hamidizad, Zeinab; Rahbari, Ali; Ghanbari, Fatemeh; Motealeghi, Zohre Aghaee (Drug Research, 2017)
Background The main side effect of gentamicin is nephrotoxicity. The effect of cobalamin (Cob) was investigated on gentamicin nephrotoxicity in rats.Methods Renal injury induced by i.p. injection of gentamicin (100 mg/kg) for 8 consecutive days. Cobalamin (6 mg/kg/day, i.p) treatment was done for 8 consecutive days as co-treatment and post-treatment protocol.Results Cobalamin significantly increased creatinine clearance levels and renal blood flow which were reduced by gentamicin. Also, cobalamin significantly improved serum electrolytes (sodium and potassium) levels which were disturbed by gentamicin. Cobalamin significantly compensated deficits in the antioxidant defense mechanisms, suppressed lipid per oxidation and ameliorated renal tissue damage mediated by gentamicin.Conclusion The results of the current study indicated that cobalamin effectively protected the kidney tissue against gentamicin induced acute nephrotoxicity in rats. The antioxidant and anti-inflammatory activities can be supposed the main factors responsible for the nephroprotective effect of cobalamin.
Keywords: cobalamin (vitamin B12); gentamicin induced nephrotoxicity; rat